FUNDAMENTALS OF ISLAM AND PEACE IN THE CONTEXT OF HADITH (Contemporary Journal of Social Science Review, 2025)
This paper, constituting Part II of the inquiry into the fundamentals of Islam and peace, shifts the analytical lens from the Quranic text to the Sunnah -  the recorded sayings, actions, and sanctions of the Prophet Muhammad (SAWA). Building upon the foundation established in Part I, which detailed the peace-oriented ethical framework of the Quran, this study examines how the Prophetic tradition (Hadith) operationalizes and reinforces these principles. Through a close reading of narrations from canonical sources such as Sahih al-Bukhari, the paper demonstrates that the Prophet’s conduct exemplified peacemaking, tolerance, compassion for all humanity, and the strict rejection of harm and aggression. It analyses key historical episodes, such as the Treaty of Hudaibiya, as paradigmatic cases of prioritizing peace over political or military advantage. Furthermore, the paper addresses the critical question of violence by contextualizing the early Islamic military engagements (Ghazwat and Sariyah), arguing they were exclusively defensive or humanitarian in nature, not expeditions for forced conversion or territorial expansion. The study concludes that the contemporary association of Islam with violence stems from a profound misrepresentation and politicisation of both scripture and history. This misrepresentation is perpetuated by extremist factions who hijack religious narrative and by external discourses of Islamophobia, obscuring the authentic, peace-centric model established by the Prophet Muhammad (SAWA).